If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (18 + 2x)(28 + 2x) = 1064 Multiply (18 + 2x) * (28 + 2x) (18(28 + 2x) + 2x * (28 + 2x)) = 1064 ((28 * 18 + 2x * 18) + 2x * (28 + 2x)) = 1064 ((504 + 36x) + 2x * (28 + 2x)) = 1064 (504 + 36x + (28 * 2x + 2x * 2x)) = 1064 (504 + 36x + (56x + 4x2)) = 1064 Combine like terms: 36x + 56x = 92x (504 + 92x + 4x2) = 1064 Solving 504 + 92x + 4x2 = 1064 Solving for variable 'x'. Reorder the terms: 504 + -1064 + 92x + 4x2 = 1064 + -1064 Combine like terms: 504 + -1064 = -560 -560 + 92x + 4x2 = 1064 + -1064 Combine like terms: 1064 + -1064 = 0 -560 + 92x + 4x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-140 + 23x + x2) = 0 Factor a trinomial. 4((-28 + -1x)(5 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-28 + -1x)' equal to zero and attempt to solve: Simplifying -28 + -1x = 0 Solving -28 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -1x = 0 + 28 Combine like terms: -28 + 28 = 0 0 + -1x = 0 + 28 -1x = 0 + 28 Combine like terms: 0 + 28 = 28 -1x = 28 Divide each side by '-1'. x = -28 Simplifying x = -28Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-28, 5}
| -4u-50=15u-35 | | 8-x=12+x | | 73+7x-4+4x=180 | | 5(x+5)+5=5x+2 | | 9/15.9=-1.79245283019 | | 9c(c-11)+10(5c+5)=3c(c+5)+c(6c-3)-30 | | g(x)=1+6x+3x^2 | | H=-16t^2+36t+61 | | 2x+4+x+1+55=180 | | 0.66667x+15=17 | | 6x^2+5x+8=0 | | 140+5x= | | 21/x=.6 | | x+5x+30=180 | | -28-6w=-21 | | 7x/-2=5 | | .5(8x-4)=10 | | x/19.7-0.609137055838 | | (w-4/9)*(-2/3)-4/5 | | d=1.7t | | 2(x+6)=4(x+1) | | H=16t^2+47t+3 | | (w-4/9)*(-2/3)--4/5 | | y=-4+1/3*(-18) | | x+(x-50)=700 | | (x+2)+(x-3)=5 | | 7=3x+5x+7 | | 70+2x+y=360 | | 107k+9-12k^2=0 | | x+(x+2)=153 | | 4t^2-28t+15=0 | | lnx+2-x=0 |